THE RECEPTIVENESS OF ISLAMIC P2P MICROFINANCING BY MALAYSIAN SMEs: AN EMPIRICAL ANALYSIS - Vanessa Clara Anak Bennet; Haneffa Muchlis Gazali (Proceeding International Seminar of Islamic Studies, 2023)
The process of acquiring loans from traditional financial institutions is arduous for SMEs during economic pressure due to time-consuming procedures accompanied by stringent application criteria. Consequently, SMEs would have a low survival rate while awaiting loan approval from traditional financial institutions. To understand the intention to use Islamic P2P microfinance, this study extended the Technology Acceptance Model (TAM) with Perceived Risks and Perceived Benefits. The current study used a quantitative research design and non-probability snowball sampling to collect data from 248 micro-entrepreneurs across Malaysia. SPSS Version 28.0 software was used to analyse the collected data. The findings indicated that this study partially supports the TAM in predicting the intention to use Islamic P2P microfinancing in Malaysia. In the case of Islamic P2P financing, perceived benefits are also found to be an important predictor. In this paper, the authors open a new avenue for Islamic contributions to the literature on entrepreneurship development. The proposed model will benefit the government as the primary policymaker, entrepreneurs, Islamic scholars and academicians.